Thermoelectric properties of non-stoichiometric CaMnO3-δ composites formed by redox-activated exsolution. Issue 4 (April 2020) - Singh, Sathya Prakash; Kanas, Nikola; Desissa, Temesgen D.; Einarsrud, Mari-Ann; Norby, Truls; Wiik, Kjell
Abstract: A novel synthesis route for preparing well-defined composites based on CMO (CaMnO3 ) has been established taking advantage of the unique phase relations in the system Ca-Mn-O at reducing- and oxidizing atmosphere, respectively. Samples corresponding to stoichiometric CMO and composites with 5 and 10 vol % of Ruddlesden-Popper (Ca4 Mn3 O10 )- and spinel (CaMn2 O4 )-phases, respectively, were prepared with final densities >91 %. The presence of secondary phases significantly enhanced the electrical conductivity compared to stoichiometric CMO. The highest electrical conductivity was observed for CMO with 10 vol % spinel varying between 55 and 75 S/cm at temperatures between 100 and 900 °C. This composition also exhibited the highest figure-of-merit ( zT ) in this study, reaching 0.083 at 800 °C.